2003
DOI: 10.1128/aem.69.1.673-678.2003
|View full text |Cite
|
Sign up to set email alerts
|

Degradation and Transformability of DNA from Transgenic Leaves

Abstract: The fate of transplastomic (chloroplast genome contains the transgene) tobacco plant DNA in planta was studied when the plant leaves were subjected to decay conditions simulating those encountered naturally, including grinding, incubation with cellulase or enzymes produced by Erwinia chrysanthemi, and attack by the plant pathogen Ralstonia solanacearum. Direct visualization of DNA on agarose gels, gene extraction yield (the number of amplifiable aadA sequences in extracted plant DNA), and the frequency that re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 34 publications
2
57
0
Order By: Relevance
“…A few published studies describe processes that limit or induce DNA release from plastids or mitochondria (Nielsen et al, 2001;Thorsness et al, 1993;Vincent et al, 1988). Ceccherini et al (2003) reported over 98% degradation of a chloroplast-harbored gene, as measured by PCR amplification, over a 72 h period in ground tobacco leaf material. Another study by the same group provided evidence that Acinetobacter sp.…”
Section: Release Of Organelle Dna From Plantsmentioning
confidence: 99%
“…A few published studies describe processes that limit or induce DNA release from plastids or mitochondria (Nielsen et al, 2001;Thorsness et al, 1993;Vincent et al, 1988). Ceccherini et al (2003) reported over 98% degradation of a chloroplast-harbored gene, as measured by PCR amplification, over a 72 h period in ground tobacco leaf material. Another study by the same group provided evidence that Acinetobacter sp.…”
Section: Release Of Organelle Dna From Plantsmentioning
confidence: 99%
“…The state of competence leading to natural transforma-bility is commonly related to the presence of competence genes, like the com genes present in Thermus thermophilus and Acinetobacter baylyi (Friedrich et al, 2001 and. The naturally transformable strain A. baylyi ADP1 (ADP1; also known as A. baylyi BD413, see Vaneechoutte et al, 2006) has been demonstrated to develop genetic competence and to be transformable in soil (Ceccherini et al, 2003;Kay et al, 2003;Nielsen et al, 2000b). Transformants successfully occurred after treatment with DNA homologous to recipient genomes (Nielsen et al, 2000a).…”
Section: Introductionmentioning
confidence: 99%
“…The data demonstrated that under specific conditions, horizontal gene transfer can take place in planta. In a second step, the in situ transformation capacity of transplastomic plant DNA was studied (Ceccherini et al 2003). Here, the DNA purified from decaying or enzymatically treated leaf tissue was found to degrade within 72 h but was able to transform in vitro the above Acinetobacter strain at a low frequency (between 10…”
Section: Biosafety Of Transplastomic Plantsmentioning
confidence: 99%